Effects of caffeic acid phenethyl ester on root canal dentin: A SEM/EDX study (Annals of Medical Research, 2021)
Aim: To evaluate the effects of Caffeic Acid Phenethyl Ester (CAPE) and its combination with EDTA and NaOCl on the surface of root canal dentine. Material and Methods: Ninety human extracted central anterior teeth were instrumented. Teeth were divided into six groups according to irrigation regime: (n=15). Group 0 (negative control) saline; group 1: 5.25% NaOCl/ distilled water (positive control); group 2: 0.5% CAPE; group 3: 5.25% NaOCl/17% EDTA; group 4: 5.25% NaOCl/0.5% CAPE and group 5: 0.5% CAPE/17% EDTA. Roots were splitted longitudinally and examined under scanning electron microscopy. Energy Dispersive X-Ray (EDX) method was used to analyse the root dentine mineral content. Results: A significant difference in smear layer (SR) was found between group 3 and group 4 (P0.05).Conclusions: In this study, CAPE did not result in better SR removal compared to NaOCl at all levels of the root canals. Overall, Group 5 was as effective as group 3 in SR removal. The mineral content of root dentin has changed.
Keywords: Caffeic acid phenethyl ester; root canal irrigant; smear layer removal; SEM-EDX